Reading the Reader: Explorations in Late Latin Poetry (KULT_online, 2016)
The dissertation The Space that Remains. Reading Latin Poetry in Late Antiquity provides an overview of different conceptions of the reader in late Latin poetry. With regard to modern literary theory Aaron Pelttari argues that the reader in late antique poetry actively participates in the literary creation of sense and meaning. On the other hand, late antique poets present themselves as readers of classical, imperial, and Christian literature.